ANALYSIS OF CONSUMER COMPLAINT BEHAVIOR AT PIZZA HUT MANADO - Tumangkeng, Jackly Jackson; Saerang, David P.E.; Tielung, Maria V.J. (Universitas Sam Ratulangi, 2019)
Abstract: Consumer complaints are classified as grievances and dissatisfaction experienced by consumers when purchasing or using certain products or services. The thing is if a customer is not satisfied with a purchase or a service they paid for and thus, customer can complain. The aim of this research is to know how is the consumer complaint behavior at pizza hut in Manado and what are the factors that make consumer complaint at Pizza Hut in Manado. To achieve these objectives the researcher got information from 10 informants using qualitative study which is in-depth interview. Through the interview from all the informants the result concluded that customers will make a complaint when customers do not feel comfortable, the foods do not suit with their taste or expectation and experiencing poor services from Pizza Hut. Some recommendations proposed for customer, it is good to know about the customer complaint because they need to understand what factors that makes them complaint. For Pizza Hut, this research may be useful in order to decrease the level of complaints and to improve Pizza Hutâ€™s performances. For the future researchers, this research hopefully will help in doing their research using the findings regarding with the topic.Â Keywords: consumer complaint, pizza hut